'Nāu te rourou, nāku te rourou, ka ora te manuhiri' ('With your food basket, and my food basket, the visitors will be fed'): Alterity, exchange and translation in Patricia Grace's Chappy (2015). Issue 1 (1st June 2022) - Orzechowska, Anna
In Chappy (2015), Patricia Grace offers an insightful glimpse into the complexities of cross-cultural communication as she recounts the vicissitudes of a Māori‐Japanese‐Hawaiian family throughout the course of the twentieth century. This article focuses on the representation of alterity as an empowering source of enrichment for individuals and communities by referencing Emmanuel Levinas's ethics of the Other. It is argued that Chappy emphasizes the significance of cherishing Otherness in its infinity, instead of attempting to enclose it in well-established frameworks. In doing so, the novel grants precedence to interaction immersed in the Levinasian 'saying' ‐ being together, listening to each other and exchanging stories, viewpoints and languages without establishing the relations of domination and subordination ‐ over communication entrenched in the 'said', whose aim is to gain the complete understanding of the Other. In this context, the article discusses the motif of translation. And while translation aims to transform the foreign into the familiar, it functions in the novel not as a tool for abolishing alterity, but as a contact zone where different cultures enter into a creative dialogue. Translating stories is portrayed as a communal activity, whereby all those involved encounter one another on equal terms, contributing their own experiences and perceptions of the world ‐ their respective baskets from the Māori proverb referred to in this article's title.